Sports Injury and Illness Epidemiology: Great Britain Olympic Team (TeamGB) surveillance during the Sochi 2014 Winter Olympic Games. Issue 1 (25th November 2014) - Palmer-Green, Debbie; Elliott, Niall
Abstract : Background: Sports injury and illness surveillance is the first step in injury and illness prevention, and is important for the protection of both athlete health and performance in major competitions. Aim: To identify the prevalence, severity nature and causes of athlete injuries and illnesses in the Great Britain Olympic Team (TeamGB) during the Sochi 2014 Winter Olympic Games. Methods: The observational prospective cohort study followed the Great Britain Injury/Illness Performance Project surveillance methodology and obtained information on injuries and illnesses that occurred during the Games between 30 January and 23 February 2014 in TeamGB athletes (n=56). Results: Among the 56 TeamGB athletes, there were 27 injuries and 11 illnesses during the Olympic Games period. This equated to 39% sustaining at least one injury and 18% at least one illness, with an incidence of 48.2 injuries and 19.6 illnesses per 100 athletes, respectively. Of all injuries and illnesses, 9% and 7%, respectively, resulted in time loss. The risk of sustaining an injury was highest for freestyle skiing, skeleton and snowboarding; and lowest for curling, biathlon and Alpine skiing (with no reported injuries); with the lower limb being the most commonly injured location. Respiratory system illnesses were most frequently reported overall, and older female athletes were the ones most affected by illness. Conclusions: The risk of injury was double the risk of illness for TeamGB athletes. Overall, the rate of time-loss issues was low. Methodological considerations are important when interpreting data, and prevention strategies should focus on those issues causing the greatest risk, in terms of prevalence and severity, to athlete health and performance.